MANAGEMENT OF WATER TREATMENT IN WASTEWATER FACILITIES THROUGH MECHATRONIC MODULES - Oybek Kholmatov; Boqiyev Abdumannob (European Science Publishing, 2024)
The article states that water treatment facilities are critical for ensuring the availability of clean and safe water. Effective management of these facilities is essential to maintain their optimal performance. With the advancement of technology, the integration of mechatronic modules has emerged as a promising solution. This article explores the application of mechatronics in water treatment facilities and discusses how these modules enhance efficiency, automation, and control. The integration of mechatronics enables automation and control systems, remote monitoring and maintenance, fault detection and diagnostics, energy optimization, and seamless integration with supervisory control systems. By leveraging mechatronics, water treatment facilities can improve operational efficiency, reduce downtime, and enhance the overall quality of water treatment processes.
Keywords: Water treatment facilities, Mechatronic modules, Automation, Control systems